Efficiency and safety of the combination of moxifloxacin, pretomanid (PA-824), and pyrazinamide during the first 8 weeks of antituberculosis treatment: a phase 2b, open-label, partly randomised trial in patients with drug-susceptible or drug-resistant pulmonary tuberculosis. Issue 9979 (2nd May 2015) - Dawson, Rodney; Diacon, Andreas H; Everitt, Daniel; van Niekerk, Christo; Donald, Peter R; Burger, Divan A; Schall, Robert; Spigelman, Melvin; Conradie, Almari; Eisenach, Kathleen; Venter, Amour; Ive, Prudence; et al.
Summary: Background: New antituberculosis regimens are urgently needed to shorten tuberculosis treatment. Following on from favourable assessment in a 2 week study, we investigated a novel regimen for efficacy and safety in drug-susceptible and multidrug-resistant (MDR) tuberculosis during the first 8 weeks of treatment. Methods: We did this phase 2b study of bactericidal activity—defined as the decrease in colony forming units (CFUs) of Mycobacterium tuberculosis in the sputum of patients with microscopy smear-positive pulmonary tuberculosis—at eight sites in South Africa and Tanzania. We enrolled treatment-naive patients with drug-susceptible, pulmonary tuberculosis, who were randomly assigned by computer-generated sequences to receive either 8 weeks of moxifloxacin, 100 mg pretomanid (formerly known as PA-824), and pyrazinamide (MPa100Z regimen); moxifloxacin, 200 mg pretomanid, and pyrazinamide (MPa200Z regimen); or the current standard care for drug-susceptible pulmonary tuberculosis, isoniazid, rifampicin, PZA, and ethambutol (HRZE regimen). A group of patients with MDR tuberculosis received MPa200Z (DRMPa200Z group). The primary outcome was bactericidal activity measured by the mean daily rate of reduction in M tuberculosis CFUs per mL overnight sputum collected once a week, with joint Bayesian non-linear mixed-effects regression modelling. We also assessed safety and tolerability by monitoring adverse events. This study is registered withClinicalTrials.gov, numberNCT01498419 . Findings: Between March 24, 2012, and July 26, 2013 we enrolled 207 patients and randomly assigned them to treatment groups; we assigned 60 patients to the MPa100Z regimen, 62 to the MPa200Z regimen, and 59 to the HRZE regimen. We non-randomly assigned 26 patients with drug-resistant tuberculosis to the DRMPa200Z regimen. In patients with drug-susceptible tuberculosis, the bactericidal activity of MPa200Z (n=54) on days 0–56 (0·155, 95% Bayesian credibility interval 0·133–0·178) was significantly greater than for HRZE (n=54, 0·112, 0·093–0·131). DRMPa200Z (n=9) had bactericidal activity of 0·117 (0·070–0·174). The bactericidal activity on days 7–14 was strongly associated with bactericidal activity on days 7–56. Frequencies of adverse events were similar to standard treatment in all groups. The most common adverse event was hyperuricaemia in 59 (29%) patients (17 [28%] patients in MPa100Z group, 17 [27%] patients in MPa200Z group, 17 [29%] patients. in HRZE group, and 8 [31%] patients in DRMPa200Z group). Other common adverse events were nausea in (14 [23%] patients in MPa100Z group, 8 [13%] patients in MPa200Z group, 7 [12%] patients in HRZE group, and 8 [31%] patients in DRMPa200Z group) and vomiting (7 [12%] patients in MPa100Z group, 7 [11%] patients in MPa200Z group, 7 [12%] patients in HRZE group, and 4 [15%] patients in DRMPa200Z group). No on-treatment electrocardiogram occurrences of corrected QT interval more than 500 ms (an indicator of potential of ventricular tachyarrhythmia) were reported. No phenotypic resistance developed to any of the drugs in the regimen. Interpretation: The combination of moxifloxacin, pretomanid, and pyrazinamide, was safe, well tolerated, and showed superior bactericidal activity in drug-susceptible tuberculosis during 8 weeks of treatment. Results were consistent between drug-susceptible and MDR tuberculosis. This new regimen is ready to enter phase 3 trials in patients with drug-susceptible tuberculosis and MDR-tuberculosis, with the goal of shortening and simplifying treatment. Funding: Global Alliance for TB Drug Development .